A methods engineering study on Quality Garments, Incorporated - Alandy-Dy, Brian Anthony R.; Ligasto, Pamela Kathleen P.; Lorenzana, Edelle A. (Diliman, Quezon City College of Engineering, 1997)
Quality Garments, Incorporated is a company engaged in direct exporting of ladies' clothing to the United States, Europe and Canada. The product line under study is the Jones NY cotton robe. The production process involves operations such as cutting, sewing, trimming, inspection, pressing, spot-washing, and packaging.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis